The Use of Literary Adaptations in the EFL Classroom: A Case Study - Beloufa, Chahra (FOSTER: Journal of English Language Teaching, 2023)
The marriage of the two arts, literature and cinema, gave birth to the production of literary adaptations, which is inspiring to explore in an EFL (English as Foreign Language) literature classroom because EFL students are becoming reluctant readers with limited critical literacy. Literary texts in print might cause a loss of interest in literature class. That is why the teacher has always secured material that will keep students' learning literature an enjoyable experience. The researcher experimented on a group of fourth-year English classical system students at Djilali Liabes University, Sidi Bel Abbes, Algeria, to bring about a change. In their British Literature classroom, one projected "Pride and Prejudice," Austen's film adaptation (2005), to observe students' abilities in criticizing the Film and discussing it and to discover to what extent it will make them eager to read the novel and get engaged. Hence, based on the structured observation during the film projection and the semi-structured questionnaires, the researcher found that Austen's adaptation was fruitful since it pushed students into critiquing what is visual and showing interest in further reading the written word. In addition, it contributed to memorizing and discovering some of the British cultural aspects of that era. Therefore, opting for a cinematic milieu in a literature classroom can have dual aims: educating and entertaining, raising students' visual awareness through readings of adaptations by concertizing what is written.